THE EFFECT OF E-SERVICE QUALITY AND PRICE ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS MEDIATING VARIABLE (A CASE STUDY ON WEBINAR SERVICE IN INDONESIAN CLINICAL TRAINING & EDUCATION CENTER (ICTEC) RSCM FKUI) - Suharyanto, Suharyanto; Vita Budi Damayanti (Dinasti Publisher, 2022)
During the COVID-19 pandemic, Information Technology (IT) is critically needed to support and improve ones performance in all matters, including services and day-to-day activities. This study aims to determine and analyze the effect of e-service quality and price on customer loyalty with customer satisfaction as mediating variable on webinar service in Indonesian Clinical Training & Education Center (ICTEC) RSCM FKUI. The technique of this study was purposive sampling and the questioner as the primary data instrument. The data was taken from 100 respondents that have participated in webinars with ICTEC RSCM FKUI. This study used SEM (Structural Equation Modeling) supported by SmartPLS application. The result of this study shows the variable of e-service quality and price has made a significant impact on customer satisfaction; the variable of e-service quality has an impact on customer loyalty; customer satisfaction has an significant impact on customer loyalty, yet the variable of price made insignificant on customer loyalty. In terms of moderation (intervening), the variable of e-service quality and price has made a significant impact on customer loyalty with customer satisfaction.